Tecnologia assistiva como recurso didático para alunos com deficiência visual no ensino de geometria euclidiana - Oliveira, Geovane Felipe Oliveira de (2024)
This work seeks to contribute to the teaching of mathematics to visually impaired students by the use of assistive technology that can be used as a teaching resource in the teaching of Euclidean geometry. used as a didactic resource in the teaching of Euclidean geometry. problem was: how low-cost materials can be applied as technology for visually impaired students in the teaching of Euclidean geometry? geometry? The general objective was to analyze the application of technology to help visually impaired students in the process of teaching and learning Euclidean geometry. process of teaching and learning Euclidean geometry. The methodology was qualitative, and the choice of this methodology is justified by the need to the need to investigate and understand educational phenomena from the perspective of the participant, in order to identify their needs in relation to the use of assistive technology in the teaching of Euclidean geometry. The research strategy was exploratory research, which in turn was used to collect information about the participant's educational needs and to develop the low-cost assistive technology resource. Case case study was used because this research was carried out with a 19-year-old blind participant blind participant who had recently graduated from elementary school. At the end of the study, after applying the Assistive Technology, there was an improvement in the visually impaired participant's perceptions and understanding of the of the visually impaired participant in the teaching and learning process of Euclidean geometry Keywords: Geometry. Assistive Technology. Visual impairment.